Geodetic investigation of landslides and land subsidence: case study of the Bhurkunda coal mines and the Sirobagarh landslide. Issue 371 (3rd March 2020) - Tiwari, Ashutosh; Narayan, Avadh Bihari; Dwivedi, Ramji; Swadeshi, Ashutosh; Pasari, Sumanta; Dikshit, Onkar
Abstract : This study presents a geodetic deformation monitoring approach and its application on two severely affected and uninvestigated study sites in India, namely the Bhurkunda coal mines in Jharkhand, and the Sirobagarh landslide in Rudraprayag, Uttarakhand. For the Bhurkunda site (characterized by underground coal mining related subsidence), a network of 56 GNSS points, densified by Total Station (TS) ground points, was set up during three field visits. GNSS derived deformation estimates reveal that the southern part of the investigated area underwent subsidence (maximum displacement 1.813 m). Furthermore, DEM differences of the three epochs generated using TS points detect a subsidence of 1.358±0.057 m with similar pattern and magnitude of movement as detected by GNSS stations. For the Sirobagarh landslide (witnessing recurring slides due to local geological conditions and rainfall), a GNSS network of six control points in an area of 500×600 m 2 was established. Deformation estimates from GNSS show subsidence in the area with a horizontal trend of movement towards the Alaknanda river situated below the landslide (maximum horizontal and vertical displacement values are 0.1306 m and 2.1315 m respectively). Further, for the Sirobagarh landslide, multi-temporal interferometry using Sentinel-1 SAR images detect displacement vectors showing downward movement of the landslide, with displacement rates ranging from 0.008 to −0.115 m yr −1 . It is evident that the landslide scarp encountered high magnitude subsidence, whereas the area containing and surrounding the landslide ( 30 km 2 ) underwent a moderate rate of subsidence. A set of surveying guidelines for monitoring deformation events of similar kind are discussed.